Covid-19 a post covid - Jekyll a Hyde moderní medicíny - Sovová, Eliška; Genzor, Samuel; Sova, Milan; Sovová, Markéta; Moravcová, Katarína; Šimek, Martin; Pyzsková, Lenka Obare (Vnitrni lekarstvi, 2022)
COVID-19 pandemic has massive impact on the whole world, lead to the death of milions of people and required excessive restrictions with large economical, psychological and other impacts. Post-COVID syndrome is defined according to the Czech pneumological and phtizeological society as a complex of symptoms persisting for more than 12 weeks from the acute stage of COVID-19 and which is not possible to explain by other causes. Exact pathopysiological mechanisms and its frequency are still not known, and the data from the literature are not consisent. We present case reports of 2 patients with very different disease and convalescence course. COVID-19 and post-COVID syndrome represent large space for the further research. The prediction of the persisting limitations and other consequencies of the diseases is still not possible. Even though there is usualy higher incidence of post-COVID symptoms in patients surviving severe COVID-19 course, the presented case reports show paradoxically exactly the oposite situation.
Keywords: case reports; pandemie; COVID-19; Pandemics; Humans; SARS-CoV-2; lidé; post‑COVID